Extensive recurrence of colon adenocarcinoma: A case of cutaneous metastasis to the legs and its clinical implication - Jeffrey Baum; Adeline Fleitz; Charles Sticco (Gastroenterology & Endoscopy)
The rate of cutaneous metastases in cancer patients overall is reported at highly variable rates, presenting in up to 5% of visceral malignancies. Colorectal carcinoma most commonly metastasizes to lymph nodes, lung, liver, and peritoneum, with only 2–6% metastasizing to the skin.1,2,3 While cutaneous metastasis of colorectal cancer most commonly spreads to the surgical scar site, metastasis to the legs, however, is exceedingly rare and only a handful of case reports are recorded in the literature.3,4,5 Early diagnosis of cutaneous metastases is critical, yet remains challenging, as a full body skin exam is not typically included in routine colon cancer surveillance. Here, we present a patient who was found to have recurrent colon adenocarcinoma with metastasis to the bilateral thighs. Our case, highlights the importance of conducting a thorough skin examination as part of routine colon cancer surveillance.